Psychotherapy for Physical Pain in Patients with Fibromyalgia: A Systematic Review - Lizzette Gómez-de-Regil; Damaris F. Estrella-Castillo (Pain Research and Management)
Objective. To provide a brief and comprehensive summary of the recent evidence from clinical trials testing psychotherapeutic interventions in patients with fibromyalgia with particular interest in their possible effect on physical pain. Methods. Bibliographical search was performed in PubMed, PsycInfo, Web of Science, Scopus, and Cochrane Library databases. Content of the manuscripts was studied to obtain, if available, the following information: year of publication, location of the research team, design, type of psychotherapeutic intervention tested, pain measures, and a brief description of the psychotherapy, groups, and outcomes regarding physical pain. Results. Initial search eliciting 475 citations got reduced to 13 relevant papers. Most research studies from Spain (n = 8) are randomized control trials (n = 10) and used guided imagery (n = 5) or cognitive behavioral therapy (n = 4). The Visual Analogue Scale (n = 4) and the Fibromyalgia Impact Questionnaire (n = 4) were the physical pain measures mostly used. Improvements on physical pain were reported on all studies with published results; nevertheless, only in five cases, differences were significant. Conclusions. Evidence on the effect of psychotherapy on physical pain in patients with FS was divergent; though most studies report a reduction in pain, this was not always lasting and/or significant. Diversity of the results might be due to the selected psychotherapeutic approaches, assessment tools, and other internal (e.g., personality traits, (sub)clinical psychiatric symptoms, and treatment adherence) and external (e.g., family environment and social support) variables worth to be considered in the future research.